Phototransistors Based on hBN-Encapsulated NiPS3 - Yingjia Liu; Xingdan Sun (Magnetochemistry, 2022)
Transition metal phosphorous trichalcogenides (MPX<semantics>3</semantics>) have been extensively investigated as photodetectors due to their wide-bandgap semiconductor properties. However, the research involved in the photoresponses at low temperatures remain blank. Here, hexagonal boron nitride (hBN)-encapsulated NiPS<semantics>3</semantics> field effect transistors were fabricated by using the dry-transfer technique, indicating strong stability under atmospheric environments. The NiPS<semantics>3</semantics> devices with the thickness of 10.4 nm, showed broad photoresponses from near-infrared to ultraviolet radiation at the liquid nitrogen temperature, and the minimum of rise time can reach 30 ms under the wavelength of 405 nm. The mechanism of temperature-dependent photoresponses can be deduced by competition between Schottky barrier height and thermal fluctuation. Our findings provide insights into superior phototransistors in few-layered NiPS<semantics>3</semantics> for ultrasensitive light detection.